Proceedings of the 31st ACM Joint European Software Engineering Conference and Symposium on the Foundations of Software Enginee 2023
DOI: 10.1145/3611643.3613888
|View full text |Cite
|
Sign up to set email alerts
|

Testing Real-World Healthcare IoT Application: Experiences and Lessons Learned

Hassan Sartaj,
Shaukat Ali,
Tao Yue
et al.

Abstract: Healthcare Internet of Things (IoT) applications require rigorous testing to ensure their dependability. Such applications are typically integrated with various third-party healthcare applications and medical devices through REST APIs. This integrated network of healthcare IoT applications leads to REST APIs with complicated and interdependent structures, thus creating a major challenge for automated system-level testing. We report an industrial evaluation of a state-of-the-art REST APIs testing approach (REST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In practice, we have observed that a physical medicine dispenser can also malfunction during testing. 22 Since medicine dispensers (or other medical devices) are not the SUT, the DT fidelity level achieved by our approach is sufficient to support the automated testing of healthcare IoT applications (SUT). Furthermore, it is worth noting that the fidelity does not decrease with the increase in the number of DTs, which is a significant benefit for testing healthcare IoT applications with hundreds of medicine dispensers.…”
Section: Results Relevance and Approach Applicabilitymentioning
confidence: 99%
“…In practice, we have observed that a physical medicine dispenser can also malfunction during testing. 22 Since medicine dispensers (or other medical devices) are not the SUT, the DT fidelity level achieved by our approach is sufficient to support the automated testing of healthcare IoT applications (SUT). Furthermore, it is worth noting that the fidelity does not decrease with the increase in the number of DTs, which is a significant benefit for testing healthcare IoT applications with hundreds of medicine dispensers.…”
Section: Results Relevance and Approach Applicabilitymentioning
confidence: 99%